PLURALISME PEMAHAMAN KEAGAMAAN SANTRI DI SURAKARTA - Kamila Adnani (al-Balagh : Jurnal Dakwah dan Komunikasi, 2016)
Islamic boarding school (Pondok pesantren) is an effective media to transform religious and cultural values. The holistic educational system design of Islamic boarding school is able to internalize some important values to santri (Islamic boarding schools students). The tolerance on the pluralism of religiosity is an important value for the moslem young generation in facing differences. The pluralism can be grown up by using some educational activities, including muhadlaroh (training of speech). The research focuses on the religious material related to pluralism in understanding religion delivered by the students of PP. Al-Muayyad and PP. Takmirul Islam Surakarta in their speeches when joining the muhadharoh. By qualitative approach, the data analysis reveals that the students of PP. Al-Muayyad and PP. Takmirul Islam Surakarta has good understanding on the pluralism of religiosity.